Perkawinan Anak: Dampaknya Terhadap Kesehatan Reproduksi dan Mental - Mardian, Andry; Mufdhalifah, Inka Winarni; Gumilar, Raden Deden; Afifah, Afifah; Desiani, Desiani (CV. Green Publisher Indonesia, 2025)
Child marriage is a serious problem in Indonesia that has a broad impact on women's lives, particularly in reproductive and mental health. This study aims to examine the impact of child marriage on reproductive and mental health through a literature review of relevant scientific articles. The method used was a qualitative literature review, reviewing articles published between 2020 and 2024. The results show that women who marry at an early age experience various reproductive complications such as anemia, miscarriage, preeclampsia, and maternal and infant mortality. Mentally, women experience anxiety disorders, stress, depression, and psychological trauma. Therefore, preventing child marriage is urgently needed to protect children's rights and improve women's quality of life.